Hydrodeoxygenation of m-cresol with Pt supported over mild acid materials - Zanuttini, María Soledad (2014)
The deoxygenation of m-cresol was studied using Pt catalysts supported on different materials of various levels of acidity, such as gamma alumina, silica, and H-BEA zeolites. The reaction was carried out at atmospheric pressure and 300 °C in a fixed-bed reactor. The catalysts were characterized by XRD, BET, TPR, TEM, H2 and CO chemisorptions, pyridine-TPD and pyridine-IR. The (metal function/acid function) ratio and the reaction conditions were adjusted in order to have a high selectivity to toluene. The effects of acid sites density, strength and type, as well as the pore structure of the different supports on the deoxygenation activity, selectivity and stability were addressed. In order to avoid the production of heavy products and a fast deactivation, the concentration of Brønsted acid sites must be very low. A high acid sites density is detrimental for catalyst stability, due to coke formation via condensation of precursors adsorbed on adjacent sites. Additionally, a mesoporous structure is better than a microporous structure regarding the stability. All the catalysts can be regenerated in air at relatively low temperature.